Seismic isolation for existing structures: a review of retrofitting techniques, case studies, and trends - Wahab Abdul Ghafar; Tao Zhong; Zhengcong Lai; Zhang Pingle; Yang Yang; Md Mehedi Hasan (Discover Civil Engineering)
Abstract A significant portion of the global building stock, particularly in seismically active regions, remains vulnerable to earthquakes because of outdated design codes, insufficient seismic considerations, and material aging. Conventional retrofitting methods are often inadequate for addressing the dynamic complexities associated with seismic loading. Seismic isolation (SI) offers a superior alternative by decoupling structures from ground motion, significantly reducing inertial forces, and enhancing the protection of structural and non-structural components. This study provides a comprehensive analysis of state-of-the-art SI techniques for retrofitting existing structures, focusing on the underlying principles of SI such as period elongation and energy dissipation. It also explored common SI system types, including elastomeric bearings (NRB, HDRB, and LRB) and sliding systems (FSB and FPS), and presented a systematic retrofitting procedure. Placement strategies (base vs. mid-story isolation) are discussed, and various international case studies (e.g., USA, Italy, China, and Japan) are examined to highlight the successful implementation and performance benefits. Despite its proven effectiveness, SI faces challenges including higher initial costs than conventional methods, technical complexities related to installation and foundation adaptation, long-term durability concerns, and regulatory barriers to its use. The review concludes by identifying emerging trends and future research directions, such as the development of advanced materials (e.g., SMAs, FREIs, and sustainable alternatives), integration of smart adaptive systems using AI and SHM, advancements in performance-based design, and expansion of applications to address climate resilience and nonstructural protection. This synthesis aims to bridge the gap between theoretical advancements and practical applications, thereby offering valuable insights into enhancing the seismic resilience of existing built environments.